Contactless, non-intrusive core temperature measurement of a solid body in steady-state. (October 2016) - Anthony, Dean; Sarkar, Daipayan; Jain, Ankur
Highlights: Presents a method to measure internal temperature of a solid body. Method utilizes appropriate integrals of measured outside temperature distribution. Method is validated for a cylindrical thermal test with embedded thermocouple. Measurements from this method agree well with thermocouple measurements. Abstract: Accurate measurement of temperature is critical for understanding thermal behavior and monitoring safety and performance of engineering systems involving heating and cooling. While a number of methods are available for measurement of temperature on the outside surface of solid bodies, there is a lack of contactless, non-invasive methods for determining temperature inside solid bodies. Development of such methods is likely to impact a wide range of engineering systems. This paper describes and validates a method for measurement of internal core temperature of a solid body in steady-state based on measurement of the temperature distribution on its outside surface based on a theoretical thermal conduction model. This method is validated by determining the steady-state core temperature of a thermal test cell using infrared temperature measurement on the surface, and comparing with measurements from an embedded thermocouple. The two measurements are found to agree well with each other in a variety of heat generation and cooling conditions. While this validation is presented for a cylindrical body, the method lends itself easily to bodies of other shapes. This work contributes towards fundamental thermal metrology, with possible applications in a wide variety of engineering systems.